Gamelan dalam Database Scopus (2010-2020): Sebuah Analisis Bibliometrik - Nurfitria, Novera Winanjar; Julia, J.; Gusrayani, Diah (Jurnal Pena Ilmiah, 2021)
The research is in the form of systematic mapping carried out with bibliometric analysis on the topic of study on gamelan in the 2010-2020 period. This study aims to obtain a description of the bibliography on gamelan topics contained in database from Scopus. This analysis was also conducted in a structured manner through four stages: (1) collecting bibliographies through Scopus metadata with the help of PoP software; (2) filling in incomplete metadata in online EndNote; (3) checking bibliographic attributes; (4) conducting bibliometric analysis with the help of VOSviewer. According to the analysis, it shows that the number of citations most often occurred in 2013. The most publication tren occurred in 2019. Wulandari D.P is the one who has the strongest collaboration ties. The most widely used title term is 'gamelan'. The most dominant abstract term is 'gamelan'. Then, the most widely used keyword term is 'music'.